2017
DOI: 10.1097/md.0000000000007036
|View full text |Cite
|
Sign up to set email alerts
|

Immature enteric ganglion cells were observed in a 13-year-old colon signet ring cell carcinoma patient

Abstract: Rationale:All the enteric ganglion cells are fully mature by 2 to 5 years of age in human. No one had reported the presentation of immature enteric ganglion cells in elder ones. Colorectal carcinoma is also rare in the adolescent population. The coincidence of these 2 rare events in a 13-year-old boy has never been reported elsewhere, which may suggest some linkage between them.Patient Concern:A 13-year-old boy presented with progressive abdominal pain and melena for 3 months. Computed tomography (CT) scan and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…[ 16 ] In 2017, Li et al provided a case report and reviewed all the literature in this area. [ 17 ] Thibodeau et al reported that a 15-year-old boy was admitted with abdominal pain and diagnosed with ascending and successfully treated colon SRCC with colectomy. [ 18 ] The patient had been alive for 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 16 ] In 2017, Li et al provided a case report and reviewed all the literature in this area. [ 17 ] Thibodeau et al reported that a 15-year-old boy was admitted with abdominal pain and diagnosed with ascending and successfully treated colon SRCC with colectomy. [ 18 ] The patient had been alive for 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…All pediatric patients detected in the past 20 years are presented in Table 2. [4,5,[13][14][15][16][17][18][19] Even the most extensive series consisted of only four cases. [16] In 2017, Li et al provided a case report and reviewed all the literature in this area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation